Chemometric classification and geochemistry of oils in the Iranian sector of the southern Persian Gulf Basin. (September 2017) - Alizadeh, Bahram; Alipour, Majid; Chehrazi, Ali; Mirzaie, Shohreh
Highlights: Two oil families are chemometrically defined in the area. Family A oils are Jurassic in age and exist in western fields. Family B oils are younger and occur in eastern fields. Geochemistry of studied oils are controlled by mixing and phase fractionation. Biodegradation is suggested to have influenced the studied oils. Abstract: Crude oil samples collected from several oilfields across the southern Persian Gulf Basin from Jurassic to Cretaceous reservoirs were chemometrically classified into two genetically distinct oil families. Family A oils, occurring in the western areas, are restricted to the Jurassic series. Family B oils, mostly occurring in the eastern areas, were generated from a younger, homogeneous marine carbonate source rock. An improved geochemical understanding of Family A oils is achieved in this study, and a refined paleo-depositional model for their source rock is presented. These high-maturity oils were generated from a Middle Jurassic carbonate source rock formed within a shallow, anoxic intra-shelf basin that was connected to the Neo-Tethys marine environment. An initial phase of biodegradation is suggested to have affected family A oils during their initial accumulation phases, but the imprint has likely been masked with mixing of multiple charges or phase fractionation. Similarly, Family B oils appear to be controlled by mixing of at least two separate charges or phase-fractionation processes, although the trap charging dynamics of the Cretaceous accumulations agrees with a stronger probability for secondary alteration processes. Based on these findings, we conclude that the present-day geochemistry of both oil families is the result of a complicated sequence of events, including mixing of at least two separate charges with varying maturities or phase separation. These new insights can have practical implications for assessing volumetric mass balance relationships in advanced hydrocarbon generation models, identifying low-risk plays, and ranking prospects.